The Genetic Variants of IKZF1 Gene Linked with the Growing Risk of Childhood Acute Lymphoblastic Leukaemia - Tayel, Safaa I.; El-Hefnway, Sally M.; Abo El-fotoh, Wafaa Moustafa M.; El-Zayat, Rania S. (Current Molecular Medicine, 2019)
Background: The zinc finger protein IKAROS (IKZF1) is an essential transcription factor in haematopoiesis that is involved primarily in lymphoid tissue differentiation. Many studies have indicated that IKZF1 alterations may be associated with acute lymphoblastic leukaemia, but the results remain controversial. Objective: We aimed to investigate the association of the rs4132601 T/G and rs10272724 T/C IKZF1 gene polymorphisms with the risk of childhood acute lymphoblastic leukaemia and to determine whether these genetic variants affect the clinical parameters and the iron profiles of these children cohort. Methods: This case control study was conducted on 170 Egyptian children comprising of two groups: group (I) included 90 children diagnosed with acute lymphoblastic leukaemia and group (II) comprised of 80 ages and sex-matched healthy control children. The studied polymorphisms were genotyped using PCR restriction fragment length polymorphism (PCR-RFLP). Results: A higher frequency of the mutant GG genotype and G allele of rs4132601 was found in the patient group than in the control group. The results also showed a significant difference among the rs10272724 genotypes, with a higher frequency of the mutant CC genotype and C allele in the patients than in controls. The mutant GG genotype of rs4132601 and the mutant CC genotype of rs10272724 were associated with a higher serum ferritin level and transferrin saturation and an older age at diagnosis of acute lymphoblastic leukaemia than the other genotypes. Conclusion: IKZF1 rs4132601 and rs10272724 could be considered significant risk contributors to childhood acute lymphoblastic leukaemia and may impact the iron profiles in these children.
Keywords: IKZF1